DEVELOPING ENTREPRENEURSHIP SKILLS OF VISUALLY IMPAIRED PERSONS OF UZBEKISTAN IN THE LIGHT OF INTERNATIONAL INTEGRATION - Kobiljon Isaev (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Current qualitative research investigated the challenges that are faced by visually impaired persons entrepreneur skills. Main purpose of the paper work is studying theoretical approaches of doing business ability of visually impaired personals and its identifying way of improvement being active in small business sector. The researcher collected secondary source data from international organization and union, local statistical information on analyzing conceptual background of current situations in Uzbekistan. Main outcomes form research are impediments to entrepreneur skills among eye problem people and its development strategies, current problems facing with generate new business entities and solutions of selected targets in Uzbekistan.